KONTRIBUSI MINAT BACA SASTRA DAN PENGUASAAN KONSEP CERPEN TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 4 MUARA BUNGO - yulia oktarina (Jurnal Tunas Pendidikan, 2019)
The purpose of this study to describe some of the following: (1) the contribution of reading literature on short story writing skills texts by students, (2) the contribution of mastery of the concept of short stories short story text writing skills by students, and (3) the contribution of reading literature and mastery of the concept of short stories short story text writing skills by students of class XI SMAN 4 Muara Bungo. This research is a type of quantitative research by using descriptive and correlation design. The data of this research is the result of a questionnaire score reading literature, scores of short stories concept mastery test results, and the results of the test scores of text short story writing skills. The findings of the study are as follows: (1) interest in reading literature gives konrtibusi to text short story writing skills by 37.21%, (2) the mastery of the concept of short stories contributed to the text of the short story writing skills by 35%, (3) interest in reading literature and mastery of the short story concept jointly contribute to the text short story writing skills by 42,25%.